Android based edutainment system (toolboxes) - Low, Wilson Kai Ming (2014)
Using games as an educational tool is not a completely new idea, neither is the concept of educational games. However it is not common in the local education scene for educators to use games as a tool for education. In this project, an Android based edutainment application will be developed as an assistive and supplementary self-access tool that students can use to bolster their knowledge of a module. It is not an unfamiliar sight that there are always students who fail to keep up with the lecturers' pace and tend to struggle badly with the module and the only available online resources are the exact copy of what goes on in the lecture. This project seeks to create a interesting and informative application that will allow such students to access additional content on their own free time to catch up with the lecturer. The Android based edutainment game is developed to allow for learning of Digital Signal Processing (DSP) through the act of playing games. The game will subconsciously train the player's mind to recognize situations where certain operations can be performed and applied.